Role of histone tails in structural stability of the nucleosome - Biswas, Mithun; Voltz, Karine; Smith, Jeremy C.; Langowski, Jörg (PLoS Computational Biology, 2011)
Histone tails play an important role in nucleosome structure and dynamics. Here we investigate the effect of truncation of histone tails H3, H4, H2A and H2B on nucleosome structure with 100 ns all-atom molecular dynamics simulations. Tail domains of H3 and H2B show propensity of -helics formation during the intact nucleosome simulation. On truncation of H4 or H2B tails no structural change occurs in histones. However, H3 or H2A tail truncation results in structural alterations in the histone core domain, and in both the cases the structural change occurs in the H2A3 domain. We also find that the contacts between the histone H2A C terminal docking domain and surrounding residues are destabilized upon H3 tail truncation. The relation between the present observations and corresponding experiments is discussed.
Gesehen am 24.03.2022